PERMAINAN TRADISIONAL SEBAGAI MEDIA STIMULASI ASPEK PERKEMBANGAN ANAK USIA DINI - Maulidia, Siti Nirmaya; Fasihah, Alya; Munawaroh, Hidayatul (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
Physical activities that are often carried out by pre-school children, such as: rolling, jumping, sliding, turning, walking, and running, are believed to be a means of stimulating the sensitivity and sensory systems of young children. This activity involves the emotions and vision of each individual. Every activity carried out contains important values for aspects of a child’s basic development. The values contained in each game can be a means of solving the problems faced.